A distal enhancer that directs Otx2 expression in the retinal pigment epithelium and neuroretina. Issue 2 (19th November 2019) - Bhansali, Punita; Cvekl, Ales; Liu, Wei
Abstract: Background: Homeodomain transcription factor Otx2 is essential for embryonic development of multiple head tissues, including retinal pigment epithelium (RPE) and neuroretina. Temporospatial regulation of Otx2 expression is critical for its functions. Molecular dissection of the cis ‐acting enhancers will help elucidate how Otx2 expression is regulated. Results: We comprehensively characterized distal enhancer hs1150 that was previously identified in a high throughput study. We established multiple transgenic mouse lines in which human hs1150, corresponding mouse hs1150, and two highly conserved sub‐fragments in the mouse hs1150 were individually fused to a minimal hsp68 promoter to drive reporter expression. We found that hs1150 enhancer directed reporter expression in the RPE, neuroretina, and brain in a developmentally regulated manner. Human hs1150 ‐directed reporter expression largely recapitulated Otx2 expression in the RPE, in the early neuroretina, and to a lesser degree in the early brain. Mouse hs1150, although shorter than human hs1150, exhibited similar enhancer activity, indicating functional conservation of hs1150 enhancer across species. Both of the highly conserved subfragments in mouse hs1150 enhancer directed reporter expression in the early neuroretina, indicating that the hs1150 enhancer has two functional components. Conclusions: Our findings provide insight into the molecular mechanisms underlying the regulation of Otx2 retinal expression. Key Findings: Otx2 expression; distal enhancer; retinal pigment epithelium; neuroretina; transgenic mice.